Design of Blockchain System for Land Services Administration at Ministry of Agrarian and Spatial Planning/National Land Agency - Suyus Windayana; M. Syamsul Ma’arif; Yandra Arkeman; Irman Hermadi (School of Business, IPB University (SB-IPB), 2024)
The objective of this study was to analyze the effectiveness of Blockchain for land services at the Ministry of Agrarian Affairs and Spatial Planning. The study was conducted using a rationalistic approach combined with a naturalistic paradigm. Data were collected through observation, stratified sampling, and systems analysis. A black box test was conducted to test the effectiveness of blockchain usage. This method was used to determine if the software was working properly. As a result, it was found that the Ministry of Agriculture and Spatial Planning/National Land Agency (Ministry of ATR/BPN) land service included target optimization divided into two subsections: time and target. Of the two subsections (time and goals), delays in the completion of land certificates and initial preparation of land certificates were found to be less effective. The problem was that there were still some land certificates for which terms and timeliness certainty were inconsistent with the Land Agency Commissioner's Decree No. 1 of 2010 on Service Standards and Land Regulations. The design of the Blockchain system for land services of the Ministry of Agrarian Affairs and Spatial Planning was developed in a limited manner based on the simplification of land data entities (in blockchain technology referred to as business objects) with the aim of illustrating how smart contracts contributed to each stage of data transactions. Thus, the Blockchain system was considered to have a high security value, especially when applied in the digital land certificate security system. Keywords: black box test, blockchain technology, land certificates, land services